Using the ADDIE Model and Universal Design for Learning Principles to Develop an Open Online Course for Teacher Professional Development. Issue 4 (2nd October 2018) - Trust, Torrey; Pektas, Emrah
Abstract: As part of a collaborative graduate course project, my students and I, Author A, sought to design an online learning experience that would support the professional growth of teachers located around the world. We used the ADDIE instructional design model and Universal Design for Learning principles to guide the development of an open online course that would meet the diverse needs of the learners. Analysis of the postcourse survey data revealed that the majority of participants who completed the course were able to achieve the course learning objectives as well as their professional learning goals. This article details the course design and facilitation process and offers insights about how to develop effective online learning experiences for educators.(Keywords: MOOC, online course, professional development, teacher learning, twitter)